1997
DOI: 10.1016/s1010-7940(96)01008-1
|View full text |Cite
|
Sign up to set email alerts
|

Pleurectomy/decortication for palliation in malignant pleural mesothelioma: results of surgery

Abstract: We conclude that pleurectomy/decortication safely provides both tissue diagnosis and effective of pleural effusion and symptoms and therefore excellent palliation in patients with MPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 18 publications
0
34
0
2
Order By: Relevance
“…At present there is an absence of randomised trials, but a national study is ongoing in the UK which is being supported by the National Cancer Research Institute comparing VATS debulking with chemical pleurodesis (MesoVATS). There are a small series of retrospective studies which provide low-grade evidence for debulking pleurectomy [44][45][46][47]. The associated morbidity of thoracotomy may diminish the benefits [48]; however there is limited but emerging evidence that VATS can provide good symptom control and may have a beneficial effect on survival [46].…”
Section: Evidencementioning
confidence: 99%
“…At present there is an absence of randomised trials, but a national study is ongoing in the UK which is being supported by the National Cancer Research Institute comparing VATS debulking with chemical pleurodesis (MesoVATS). There are a small series of retrospective studies which provide low-grade evidence for debulking pleurectomy [44][45][46][47]. The associated morbidity of thoracotomy may diminish the benefits [48]; however there is limited but emerging evidence that VATS can provide good symptom control and may have a beneficial effect on survival [46].…”
Section: Evidencementioning
confidence: 99%
“…complete macroscopic cytoreduction is unattainable, unless the disease is minimal and localized. 7) EPP, by contrast, provides more radical cytoreduction, including disease in the diaphragm and pericardium. The result of the current study demonstrated that in a large series of selected patients, EPP is independently associated with a marked improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In the past, the role of surgery in the management of this disease was mainly to establish the diagnosis and provide palliation of dyspnea by using pleurodesis, pleurectomy and/or decortication. [5][6][7] There have been no randomized trials reported, but it is likely that the survival outcomes after these palliative procedures are little different from the natural course of the disease. 2,8) Due to the locally aggressive nature of MPM, thoracic surgeons have focused much effort on improving the surgical techniques to provide maximal tumor clearance, and as a result, extrapleural pneumonectomy (EPP) has been utilized as the cytoreductive procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with high procedure-associated morbidity (~50 %) and mortality (4-15 %) [69], EPP is generally discouraged [67•]. In contrast, pleurectomy with decortication palliates such symptoms as dyspnea, chest discomfort, and recurrent pleural effusions with significantly less operative risk than EPP [70].…”
Section: Pleural Thickeningmentioning
confidence: 99%